PENERAPAN PRINSIP KOMUNIKASI ISLAM DALAM INTERAKSI SESAMA MAHASISWA PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM IAIN PONTIANAK - Rita Tatalia; Muhammad Habibi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This study aims to determine the principles of Islamic communication used in the interaction relationship, to determine the supporting factors that influence students in the application of Islamic communication principles and the inhibiting factors. What are the principles of Islamic communication used, how students apply the principles of Islamic communication and the supporting and inhibiting factors. This research was conducted with a qualitative approach with a descriptive method. The results showed that: (1) the principles of Islamic communication used by students in interacting with each other were the principle of honesty, the principle of cleanliness and the principle of positive speech; 2) students apply the principles of Islamic communication in their interactions with fellow students or the campus environment by creating good communication, but students are not fully able to apply the principles of Islamic communication; (3) the supporting factors in the application of the principle are the ability to communicate, remind each other, adaptability and increase reading. While the inhibiting factors that influence the application of Islamic communication principles are the lack of student awareness, self and environmental factors in applying Islamic communication principles.